2022
DOI: 10.21608/ejprs.2022.220428
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Comparative Study between Muscle Flaps and Fasciocutaneous Flaps in Reconstruction of Chronic Osteomyelitis Related Wounds of the Lower Limb in the Adult Population

Abstract: Introduction: Chronic osteomyelitis cases are challenging, as they require a multidisciplinary approach for reconstructive soft tissue coverage and orthopedic management. Proper debridement, stable coverage and effective antibiotic therapy are mandatory before application of flap coverage. Patients and Methods:We performed a retrospective comparative study between muscle and fasciocutaneous flaps used for coverage of chronic osteomyelitis related wounds of the lower limb. It included thirty patients who finish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Successful osteomyelitis clearance following reconstruction is difficult to definitively declare due to quiescent phases as well as variation in symptomatology and duration, ultimately leading to high relapse rates. 26 Current clinical evidence assessing recurrence in the literature is limited to heterogeneous patient populations and operative indications, as exemplified by the aforementioned study by Khatter et al 19 However, the recurrence rate observed in the current study remained comparable to the traumatic population and higher than heterogenous populations. 21,27,28 One reason for this is that the current study encompasses solely high-risk patients as diabetes and PVD elevate risk of recurrence.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…Successful osteomyelitis clearance following reconstruction is difficult to definitively declare due to quiescent phases as well as variation in symptomatology and duration, ultimately leading to high relapse rates. 26 Current clinical evidence assessing recurrence in the literature is limited to heterogeneous patient populations and operative indications, as exemplified by the aforementioned study by Khatter et al 19 However, the recurrence rate observed in the current study remained comparable to the traumatic population and higher than heterogenous populations. 21,27,28 One reason for this is that the current study encompasses solely high-risk patients as diabetes and PVD elevate risk of recurrence.…”
Section: Discussionmentioning
confidence: 45%
“…[15][16][17][18] A review of the literature revealed only Khatter et al directly compares outcomes in patients who receive muscle or fasciocutaneous flaps for LE soft tissue coverage with chronic osteomyelitis, in which the authors report comparable complication rates and aesthetic results. 19 However, this study consisted of a limited traumatic patient population, and notably did not report on the efficacy of the two flap types in achieving limb salvage, ambulation, or osteomyelitis recurrence rates. Additional studies looking at the traumatic patient population showed that there were no significant differences in between muscle and fasciocutaneous free flaps.…”
mentioning
confidence: 99%